Catalytic Performance of Co3O4 on Different Activated Carbon Supports in the Benzyl Alcohol Oxidation - Cordoba Arroyo, Misael (2017)
Co3O4 particles were supported on a series of activated carbons (G60, CNR, RX3, and RB3). Incipient wetness method was used to prepare these catalysts. The effect of the structural and surface properties of the carbonaceous supports during oxidation of benzyl alcohol was evaluated. The synthetized catalysts were characterized via IR, TEM, TGA/MS, XRD, TPR, AAS, XPS, and N2 adsorption/desorption isotherm techniques. Co3O4/G60 and Co3O4/RX3 catalysts have high activity and selectivity on the oxidation reaction reaching conversions above 90% after 6 h, without the presence of promoters. Catalytic performances show that differences in chemistry of support surface play an important role in activity and suggest that the presence of different ratios of species of cobalt and oxygenated groups on surface in Co3O4/G60 and Co3O4/RX3 catalysts, offered a larger effect synergic between both active phase and support increasing their catalytic activity when compared to the other tested catalysts.